2020
DOI: 10.21037/tcr.2019.12.04
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic and ultrastructural analysis of Clara cell and type II alveolar epithelial cell-type lung cancer cells

Abstract: Background: Currently, the identification of Clara cell and type II alveolar epithelial cell-type cancer cells requires electron microscopy, which is a time-consuming and expensive process involving a complicated tissue sampling procedure. The aim of this study was to identify unique biomarkers for Clara cell and type II alveolar epithelial cell-type lung cancer cells, respectively, with proteomic profiling.Methods: Six human lung adenocarcinoma cell lines (A549, NCI-H358, NCI-H1650, HCC827, NCI-H1395, and NCI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…Because of the late-stage diagnosis and the inadequate treatment choices, the survival rate is subpar, and as a result, screening for novel biomarkers is critical for the early detection of lung cancer. Hou et al [52] studied cell-type lung cancer cells proteome profile and observed that five differentially expressed proteins, including ubiquitin carboxyl-terminal hydrolase isozyme L1 (UCHL1), cytokeratin 19 (CK19), cytokeratin 8 (CK8), ERO1L, and peroxiredoxin 2 (PRDX2), were significant between NCI-H358 and A549 cells. None of them demonstrated applicability as a reliable lung cancer biomarker.…”
Section: Lung Cancermentioning
confidence: 99%
“…Because of the late-stage diagnosis and the inadequate treatment choices, the survival rate is subpar, and as a result, screening for novel biomarkers is critical for the early detection of lung cancer. Hou et al [52] studied cell-type lung cancer cells proteome profile and observed that five differentially expressed proteins, including ubiquitin carboxyl-terminal hydrolase isozyme L1 (UCHL1), cytokeratin 19 (CK19), cytokeratin 8 (CK8), ERO1L, and peroxiredoxin 2 (PRDX2), were significant between NCI-H358 and A549 cells. None of them demonstrated applicability as a reliable lung cancer biomarker.…”
Section: Lung Cancermentioning
confidence: 99%
“…This conclusion was compatible with Reznik-Schuller (1976) who observed that long-term administration of nitrosamine derivatives to hamster rats, results in the production of bronchogenic carcinomas composed of neoplastic Clara cells. Tumor cells of the Clara cell type have a cluster of electrondense secretory granules, whereas tumor cells of the type II alveolar epithelial cell type have lamellar inclusion bodies inside the cytoplasm (Hou et al, 2020).…”
Section: Thementioning
confidence: 99%